Investigation on Mechanical Properties of Reactive Powder Concrete under Different Curing Regimes. (2017) - Hiremath, Parameshwar; Yaragal, Subhash C.
Abstract: Reactive Powder Concrete (RPC) is a form of Ultra High Performance Concrete (UHPC). The main constituents of RPC are cement, sand, silica fume, steel fiber and quartz powder with minimal water to binder ratio, without coarse aggregate. Due to its dense microstructure, RPC exhibit superior properties such as higher strength, durability and long term stability. Earlier researchers have produced RPC with Compressive strength up to 800 MPa and flexural strength of 75 MPa. In the present study, locally available materials are used to produce RPC of different mix proportions. The main objective is to study the effect of different curing regimes on the strength of RPC. The durability study is also carried out by way of accelerated corrosion test and acid test. Results have shown considerable enhancement in compressive strength when RPC specimen were subjected to hot air curing of different durations. RPC specimen cured under hot air curing and steam curing shown better performance compared to normal curing and air curing. Also RPC has shown better resistance to sulphate attack; further the rate of corrosion is low compared to high performance concrete.